PP75 What Factors are Important in Smoking Cessation and Relapse in Women from Deprived Communities? – A Qualitative Study. (10th September 2013) - Barber, J; Rumsby, E; Parker, S; Mohebati, L; Venables, S; Lawson, K; Scanlon, T; Memon, A
Abstract : Background: It is well established that women start to smoke earlier, are more susceptible to smoking-related disease and find it harder to quit than men. However, little research exists on factors associated with smoking cessation and relapse in women, particularly those from deprived communities. We conducted a qualitative study in South East England to examine these factors. Methods: Eleven women who had used the NHS Stop Smoking Service in East Sussex were engaged in focus group discussions. Data were subjected to manual and NVIVO software-based thematic analysis. Results: Women confirmed that it is harder for them to quit smoking than men. A number of gender-specific themes were identified for this perceived difference. Women felt that post cessation weight gain was inevitable and acted as a barrier to quitting. Menstrual fluctuations and greater levels of stress were perceived as obstacles to quitting and reasons for relapse. Conversely, the women cited the effects of smoking on appearance, and guilt about exposing young children to passive smoking as powerful motivators to stop and highlighted the force of public health campaigns that focused on these factors. Whilst participants agreed that female smoking is still stigmatised it was not clear if this motivates cessation. The study exposed divergent views on whether quitting with someone close to you is a help or hindrance. Other non-gender specific themes including alcohol intake, daily routine and being in the presence of smokers all emerged as situational triggers of relapse. Discussion: These findings support consideration of issues around weight gain, menstrual fluctuations, stress, appearance, stigma and guilt about exposure of young children to passive smoking in the design of public health campaigns and interventions. Female-specific policy/programmes have been shown to facilitate cessation in women, and more research is needed on how to limit the impact and perception of post-cessation weight gain, stress and menstrual fluctuations on cessation attempts and relapses. This study and previous research suggest that national campaigns focusing on appearance and the effect of passive smoke on children may alter behaviour. However, more research is needed to understand how altered appearance can be made more relevant to younger women, and whether mass media specifically targeted at women is more effective at changing female smoking behaviour. Low socioeconomic status and deprivation are the strongest predictors of smoking in women, and more research is needed into how services and interventions can be best designed to impact on women living in deprived communities.